Functionalized Carbon Nanotubes: Emerging Applications in the Diverse Biomedical Arena - Singhai, Nidhi J.; Ramteke, Suman (Current Nanoscience, 2020)
Background: In recent times, CNTs have been much explored, and a topic of interest in science and technology and not limited to any specific field. The diverse application area included field emission, energy storage, atomic electronics, nuclear force microscopy, and imaging. In biology, CNTs engaged in developing novel tools for the delivery of biologically important molecules as well as in diverse biomedical arenas. However, despite their promise, studies of the interaction of CNTs with biological systems most often resulted in cytotoxicity at an early stage, and problems relevant to the safety and biological compatibility of CNTs are of greatest importance. The toxic effects of carbon nanotubes (CNTs) are required to be either evaded, diminished, or decreased up-to clinical acceptance level. However, rich surface chemistry that CNTs possess can be employed to functionalize them as per the specific biomedical requirements which may be useful to overcome toxicity issues. Objective: To explore the recent reports on the functionalized CNTs for a variety of biomedical applications such as biosensing, electrochemical detection of drug, bone tissue engineering, and vitamin detection. Results: Most of the cited articles reveal that the functionalization of CNTs may reduce its toxicity and enhance its utilization in different biological applications. Conclusion: The review successfully frames to provide novel applications of functionalized CNTs in the biomedical arena including detection of vitamins, bone tissue engineering, electrochemical determination of drugs, and development of biosensors along with a discussion on current patent and clinical trial status of functionalized CNTs.
Keywords: toxicity